Empirical analyses of the financial experiences of Mexico and Jamaica in the mid 1990's : lessons for the Caribbean - Ghartey, Edward E. ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Examines the reason why Jamaica was able to withstand the numerous bank failures, avert financial crisis and solve the problem internally; while Mexico was not able to avert its financial crisis without outside assistance. Seeks to draw important lessons for the Caribbean.